The Development of Islamic Maritime Civilization on the East Coast of Sumatra during 17th-18th Centuries - Muhammad Affan; Ajid Thohir; Hamdani; Ahmad Suaedy (UIN Raden Mas Said Surakarta, 2023)
Abstract The following research aims to discuss the development of Islamic maritime civilization on the East Coast of Sumatra during the 17th to 18th centuries AD. What sultanates represented the Islamic maritime civilization on the East Coast of Sumatra from the 17th to the 18th century AD and what were the characteristics of the Islamic maritime civilization on the East Coast of Sumatra that developed during this period are the two questions raised in this research. To answer these two questions, this research uses the historical research method with research steps that include heuristics, criticism, interpretation, and historiography. The search for sources was conducted through literature research. The results of the research itself are expected to have positive implications for the development of the history of Islamic civilization in the archipelago, especially in the field of Islamic maritime civilization which has been neglected. The research concluded that the Islamic maritime civilization on the East Coast of Sumatra was represented by sultanates such as Aceh, Siak, Deli, Serdang, Langkat, and Asahan. These sultanates were sultanates with brown water civilization because they placed the center of their power downstream of the river. Nevertheless, their maritime capabilities have reached green water cruising and blue water cruising. Keywords: Islamic maritime civilization, Islamic history, maritime history, sultanates, East Coast of Sumatra